2019
DOI: 10.1111/iep.12298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three‐month streptozotocin‐induced diabetes in mice on blood platelet reactivity, COX‐1 expression and adhesion potential

Abstract: Diabetes is associated with an increased risk of cardiovascular disease. This is partially attributed to an altered activation status of blood platelets in this disease. Previously, alterations have been shown in COX-1 and protease activated receptor (PAR)-3 receptor expression in platelets in two animal models of diabetes, there have not been studies which address expression of these proteins in mice with long-term streptozotocin (STZ)-induced diabetes. We have also addressed the effect of diabetes on platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…At the same time, there are conflicting reports on platelet adhesion under flow conditions in vitro in animal models of diabetes. No such increased interactions were observed in our previous in vitro studies in mice with 3-month STZ-induced diabetes [28]. However, it was recently shown that platelets from STZ diabetic mice adhered to a higher extent to fibrinogen in flow conditions in vitro [29].…”
Section: Evaluation Of Adhesion Potential Of Platelets From Diabetic Patientsmentioning
confidence: 57%
“…At the same time, there are conflicting reports on platelet adhesion under flow conditions in vitro in animal models of diabetes. No such increased interactions were observed in our previous in vitro studies in mice with 3-month STZ-induced diabetes [28]. However, it was recently shown that platelets from STZ diabetic mice adhered to a higher extent to fibrinogen in flow conditions in vitro [29].…”
Section: Evaluation Of Adhesion Potential Of Platelets From Diabetic Patientsmentioning
confidence: 57%
“…According to Przygodzki et al, 14 platelets of mice with 3 months of STZ‐induced diabetes show increased COX‐1 expression and TXA1 production, like other diabetic animal models. However, they differ from the deb/deb mouse model of diabetes, in terms of the simultaneous basal activation and reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…These two phenomena lead to proaggregatory prostanoids being more prevalent than antiaggregatory prostanoids. Additionally, platelet reactivity increases their ability to adhere to blood vessel walls, which contributes to atherosclerosis 13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study shows that in mice with streptozosocin-induced diabetes, platelets have more frequent interactions with endothelial vessels. This interaction is due to increased expression of vWF in endothelial cells and is mediated by platelet GPIb-IX-V [71].…”
Section: Platelet Gpib Hyperreactivity In T2dm and Its Role In The Pa...mentioning
confidence: 99%